An American Story - Alexander, Kwame; Coulter, Dare (New York : Little, Brown and Company, 2023)
"A picture book in verse that threads together past and present to explore the legacy of slavery during a classroom lesson"--
Keywords: Juvenile literature. -- History -- United States; Juvenile literature. -- Civil rights; Juvenile literature. -- Social conditions; Juvenile literature. -- Politics and government; Racism -- Juvenile literature. -- History -- United States; Slavery; African Americans; Racism; United States -- Juvenile literature. -- Race relations; United States -- Race relations